Fertility Outcome in Polycystic Patient after Bariatric Surgery - Shah Abbas, Nazia Sayed, Reema Fateh, Inayatullah Khan, Mohammad Usman (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Medically induced weight loss often restores ovulation among polycystic ovarian syndrome (PCOS) women with obesity. Women with PCOS are more likely to be obese and have abdominal fat than women without PCOS, which is the most prevalent metabolic condition in premenopausal women. The present study aimed to determine the fertility outcome in polycystic obese women after bariatric surgery. Patients and Methods: This cohort study was conducted on 56 polycystic women with obesity undergoing bariatric surgery in the bariatric surgery department of Luqman International Hospital, Saidu Sharif Swat for the duration from 2017 to 2022. Polycystic patients were investigated for main outcome such as liver birth rates and pregnancy. SPSS version 26 was used for data analysis. Results: The live birth rates and pregnancy rates in PCOS women seeking fertility were 83% and 94.8% whereas in control cases were 77.6% and 68.4% respectively. PCOS women took 34 ± 26 months to get pregnant for the first time following surgery, and controls took 31 ± 24 months. There was no significant difference between PCOS neonates and controls in terms of their birth weight means (2856 + 624 g vs. 3246 + 592 g), but the number of newborns with low birth weights was similar between the two groups. Maternal problems (18.4% in PCOS and 23.6% in controls) and newborn complications (24.6% in PCOS and 15.4% in controls) were uncommon, with no differences between groups. Conclusion: Women with PCOS were more likely to have high fertility rates after bariatric surgery, especially in those seeking fertility, with no difference between those with hyper androgenic PCOS and those without. There were few maternal or neonatal complications such as preeclampsia and gestational diabetes associated with these pregnancies. Keywords: Bariatric surgery, Polycystic patients, Obesity, Fertility outcome